2018
DOI: 10.1590/s1678-9946201860034
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical profile of HIV-infected patients from Southwestern Goias State, Brazil

Abstract: Knowledge about epidemiological distribution patterns of HIV infection in different geographic regions is relevant to understand the dynamics of the disease in Brazil. This study aims to characterize the epidemiological and clinical profile of HIV-infected patients from Southwestern Goias State, from 2005 to 2015. A standardized questionnaire was used to collect clinical-epidemiological, virological, and immunological data from the medical records of all HIV-infected patients (n=539) who were followed at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 25 publications
3
13
0
9
Order By: Relevance
“…A previous study at Clinical Hospital Doutor Serafim de Carvalho, Southwestern Goias, Brazil [16] found the mean age of presentation was 39.5±11 with male predominance, heterosexual route as a common mode of transmission in HIV patients, these findings were in concordance with our study. This study also [16] found pneumonia caused by Pneumocystis jirovecii was the most predominant OI, while in our study, tuberculosis was common OI among HIV patients. Our study's limitation was that it was conducted at a single tertiary care center with limited sample size.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A previous study at Clinical Hospital Doutor Serafim de Carvalho, Southwestern Goias, Brazil [16] found the mean age of presentation was 39.5±11 with male predominance, heterosexual route as a common mode of transmission in HIV patients, these findings were in concordance with our study. This study also [16] found pneumonia caused by Pneumocystis jirovecii was the most predominant OI, while in our study, tuberculosis was common OI among HIV patients. Our study's limitation was that it was conducted at a single tertiary care center with limited sample size.…”
Section: Discussionsupporting
confidence: 93%
“…In this systematic review, we included two RCTs matching the above inclusion criteria. These trials sourced data from about 833 COVID-19 patients from 115 hospitals in Asia, Europe, and the US [15,16]. In both the trials, the patients received the intravenous remdesivir of 200 mg on the first day and 100 mg on the successive nine days [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations